Specialties of First SMED in Pharmaceutical Manufacturing - Bene, Ágnes; Bene, Péter (International Journal of Engineering and Management Sciences, 2016)
Single Minute Exchange of Die (SMED) is considered as an effective lean management method increasingly used in pharmaceutical manufacturing. By reducing change-over times and costs, the successful implementation of the first SMEDs may bring a significant increase in terms of manufacturing flexibility. The purpose of this study is present the special factors that fundamentally determine SMEDs applied especially in the process of pharmaceutical manufacturing. By focusing on a well defined part of the pharmaceutical manufacturing process, lasting from Weighing and Measuring to the end of Tablet Pressing, the study also aims to highlight the benefits of SMED itself. The findings of the research are based on the practical experiences of four SMEDs implemented in various sections of production. According to the experiences and considering industrial specialties, the implementation of SMED has to harmonise with the requirements of Good Manufacturing Practices (GMP) which are representing the golden quality standards of pharmaceutical manufacturing.